Practical Application of the Tourism Carrying Capacity Concept in Cultural Tourism : Example of the Maritime Museum of Montenegro - Petronijevic, Aleksandra (Turizam, 2022)
Until 2019, picturesque nature, interesting geographical position and rich cultural heritage of Kotor kept attracting many visitors, resulting in an increasing number of visits to the Old Town and Maritime Museum of Montenegro, situated in Kotor. Currently (2020), the global pandemic brought everything to a halt, but once tourism starts recovering again the issue of sustainable management of tourism flows and use of cultural resources in Kotor will inevitably arise again. Since the Maritime Museum is included among the most popular visiting points in Kotor, this research aims to assess its real carrying capacity in order to compare the results to the official visitor statistics and determine whether the Museum, once the noble captain family Grgurina’s home, with its valuable collections is exposed to high tourism pressure. The results indicated that, although visitor numbers were continuously rising in previous years, the Maritime Museum, together with its valuable collections, was not subject to overconsumption or “overtourism”, since the total number of realized visits in general, and visits by tourists organised in guided groups during 2019, was below the Museum’s real carrying capacity. This paper builds on existing knowledge about the tourism carrying capacity in cultural tourism in Montenegro, suggests and elaborates concrete and replicable calculation methods, and offers useful data for sustainable management of heritage sites and strategic planning of tourism flows.  Keywords: cultural heritage, real carrying capacity, sustainable management
Keywords: cultural heritage; real carrying capacity; sustainable management